Pursed-Lip Breathing Technique in Increasing Oxygen Saturation and Decreasing Dyspnea in Patients with Chronic Obstructive Pulmonary Disease: Literature Review - Aisya Rahmadhanty (Universitas Muhammadiyah Semarang, 2022)
COPD is characterized by persistent respiratory symptoms and airflow limitation due to blocked airways and alveolar abnormalities caused by noxious particles or gases that can lead to hypoxemia and progress to hypoxia which will result in decreased oxygen saturation and shortness of breath. Actions in overcoming shortness of breath and decreasing oxygen saturation can be done non-pharmacologically, namely the Pursed-Lip Breathing (PLB) technique. This study aims to determine the effect of PLB on increasing oxygen saturation and reducing shortness of breath in COPD patients. This literature review is a search of electronic databases, namely SAGEPub, Pubmed, Science Direct, Wiley Online Library, ProQuest, and DOAJ. The search for articles published from 2016-2021 found 10 relevant articles. The result is that PLB is effective in reducing the physical responses of COPD patients such as hemodynamics, increasing oxygen saturation, and controlling symptoms of shortness of breath. While the psychological response can increase the self-efficacy of COPD sufferers. In conclusion, this PLB technique can be used by nurses as a non-pharmacological approach and reduce negative physical and psychological responses in COPD sufferers.